Chicoric acid: chemistry, distribution, and production - Lee, Jungmin; Scagel, Carolyn F. (Frontiers in Chemistry, 2013)
Though chicoric acid was first identified in 1958, it was largely ignored until recent popular media coverage cited potential health beneficial properties from consuming food and dietary supplements containing this compound. To date, plants from at least 63 genera and species have been found to contain chicoric acid, and while the compound is used as a processing quality indicator, it may also have useful health benefits. This review of chicoric acid summarizes research findings and highlights gaps in research knowledge for investigators, industry stakeholders, and consumers alike. Additionally, chicoric acid identification and quantification methods, biosynthesis, processing improvements to increase chicoric acid retention, and potential areas for future research are discussed.